Junior Farmer Field and Life Schools: Experience from Mozambique - Djeddah, Carol; Mavanga, Rogério; Hendrickx, Laurence (International Food Policy Research Institute, 2006)
In the last 20 years HIV/AIDS has progressed from seemingly isolated small epidemics to a more generalized epidemic. In countries hard hit by the epidemic, HIV/AIDS continues to contribute to the problems faced by youth. A serious consequence of the AIDS epidemic is the growing number of AIDS orphans. In 2003 there were a total of 43 million orphans in Sub-Saharan Africa, of whom 12.3 million were orphaned by AIDS. It is estimated that in the region, by 2010, orphans from all causes will total 50 million, of whom 18.4 million will have lost one or both parents to AIDS (UNAIDS/UNICEF/USAID 2004). Recent data suggest that in some highly HIV/AIDS-impacted countries the prevalence of orphans is higher in rural than urban areas (UNICEF 2003).